2013
DOI: 10.1172/jci65260
|View full text |Cite
|
Sign up to set email alerts
|

Specialized role of migratory dendritic cells in peripheral tolerance induction

Abstract: Harnessing DCs for immunotherapies in vivo requires the elucidation of the physiological role of distinct DC populations. Migratory DCs traffic from peripheral tissues to draining lymph nodes charged with tissue self antigens. We hypothesized that these DC populations have a specialized role in the maintenance of peripheral tolerance, specifically, to generate suppressive Foxp3 + Tregs. To examine the differential capacity of migratory DCs versus blood-derived lymphoid-resident DCs for Treg generation in vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
299
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(318 citation statements)
references
References 60 publications
13
299
3
3
Order By: Relevance
“…1C, 1D). This observation is consistent with previous studies (25) in that high steady-state expression levels of DEC205 (Supplemental Fig. 1A) correlate with the preferential uptake of the anti-DEC205 Ab in vivo (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1C, 1D). This observation is consistent with previous studies (25) in that high steady-state expression levels of DEC205 (Supplemental Fig. 1A) correlate with the preferential uptake of the anti-DEC205 Ab in vivo (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Recombinant anti-DEC205 Abs fused to disease-relevant autoantigens have been developed and used successfully for tolerogenic protection in autoimmune disease models, including autoimmune diabetes (24,26) and EAE (14,18,25). In the present study, we show that administration of a single dose of recombinant anti-DEC205 Ab fused to the cartilage-derived immunodominant PG 70-84 efficiently ameliorates the severity of PG-induced arthritis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Indeed, DC-based therapy has been proposed to restore tolerance in the context of several autoimmune diseases (20)(21)(22). The two main strategies developed are the direct targeting of Ags to + steady state DCs (11,(23)(24)(25)(26) and the repetitive injection of tolerogenic DCs (27)(28)(29). We have previously demonstrated that repetitive injection of immature and semimature DCs can prevent adverse clinical outcome and protect mice from experimental collagen-induced arthritis (CIA) (30,31).…”
Section: R Egulatory T (Treg) Cells Actively Suppress Pathologicalmentioning
confidence: 99%
“…Secondly, and of relevance to transplantation, they aid in peripheral tolerance. They do this by the presentation of antigens while lacking the co-stimulatory molecules required for T cell activation [32,33] . This causes T cell unresponsiveness as well as Treg induction [33] .…”
Section: Dendritic Cellsmentioning
confidence: 99%